Penggunaan Metode Card Sort untuk Meningkatkan Hasil Belajar Materi Mari Belajar QS. at-Tin Kelas V SD Negeri Penundan Banyuputih Batang - Krisiati; Basith, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The background of this research is the PAI learning conditions in the Let's Learn Qs At Tin material at Penundan State Elementary School which shows that the students' ability to collaborate, activeness and PAI learning outcomes are still relatively low. As proof, students' daily test scores are low as indicated by the number of scores below the PAI KKM. Therefore, it is hoped that the application of the card sort learning method can help students' understanding of the PAI Let's Learn Qs At Tin subject so that researchers are interested in researching the research problem of whether the card sort method can improve student learning outcomes. The type of research used in this research is classroom action research which consists of two cycles. The target of this research was class V students at Penundan State Elementary School, consisting of 11 male students and 9 female students. Based on the research results, the average in the pre-cycle was 61.50 with a classical completeness percentage of 40%, the average student learning outcome in cycle I was 71.25 with a classical completeness percentage of 65%, and the average student learning outcome in cycle II amounting to 88.25 with a classical completion percentage of 90%. From the data above, it can be concluded that applying the card sort learning method has been proven to improve learning outcomes for the Let's Learn Qs At Tin material in Class V of Penundan State Elementary School.